Perancangan Aplikasi Komik Hadist Berbasis Multimedia - Helmi Fauzi Siregar; Yustria Handika Siregar; Melani Melani ((JurTI) Jurnal Teknologi Informasi, 2018)
Abstract - Comics are visual communication media that contain information, ideas, messages that are poured into images as attractive as possible. The combination of comics and hadiths is suitable to be used as an alternative to da'wah media because there are moral and moral messages contained in hadiths. The hadith comic application is made to make it easier for readers to understand the contents of comic stories and minimize the common mistakes that often occur. The method used in making the application is to use PHP. The hadith comic application has the features of presenting comics collaborated with animation, this is so that users listen to the comic storyline correctly and sequentially so as to minimize failure in understanding the core story. Hadist comic applications accompanied by attractive images and color variations make it an interesting application to use especially for teenagers and children. Keywords - Applications, Comics Hadits, Information, Multimedia